ChemInform Abstract: Amide and Peptide Bond Formation in Water at Room Temperature. Issue 2 (23rd December 2015) - Gabriel, Christopher M.; Keener, Megan; Gallou, Fabrice; Lipshutz, Bruce H.
Abstract: A general and environmentally benign method for the formation of amide/peptide bonds in aqueous medium is presented.